48/(x^1/3) - 6 = 0

Now multiply by x^1/3 on both sides, we get

x^1/3 *[48/(x^1/3) - 6] = 0 * x^1/3

48 - 6x^1/3 = 0

Now add 6x^1/3 on both sides, we get

48 - 6x^1/3 + 6x^1/3 = 0 + 6x^1/3

48 = 6x^1/3

Now divide by 6 on both sides , we get

48/6 = 6x^1/3 / 6

8 = x^1/3

Now take Cube on both sides , we get

(8)^3 = (x^1/3)^3

512 = x

Hence x = 512

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up